Chinese strategy and military modernization in 2015 a comparative analysis - Cordesman, Anthony H.; Colley, Steven; Wang, Michael (Center for Strategic & International Studies Rowman & Littlefield, 2015)
This study is intended to support a dialogue among China, the United States, and other key Asian powers. It focuses on the current developments in China's military strategy, forces, and modernization, but in the context of how they are influencing U.S. strategy and force development and the reactions of Japan, South Korea, and Taiwan